Social Support and Stress Symptoms of Lupus Patients - Nugraha, Suci; Srisayekti, Wilis (ANIMA Indonesian Psychological Journal, 2012)
The effects of social support on reducing the stress symptom of lupus patient were shown by Nugraha (2005). This article was intended to describe the social support used during the social support activities. In this study social support was given to two lupus patients during 12 weeks (once a week, two hours max. every session), applying the one-to-one method and helping techniques from Brammer (2003). The results described that support techniques mostly used to fulfil the patients’ needs for emotional and informational supports were attending, reassuring, and summarizing; whereas the supports mostly used were the roles as a friend who listened to the patient, who encouraged them and who gave them information related to lupus. The descriptions also revealed that the author needed several sessions to show that social support affects the patients. Penelitian Nugraha (2005) memperlihatkan bahwa pemberian dukungan sosial mengurangi keluhan simptom stres penderita lupus. Artikel ini bermaksud menggambarkan dukungan sosial dalam aktivitas pemberian dukungan sosial tersebut. Pada studi ini dukungan sosial diberikan terhadap dua penderita lupus selama 12 minggu (satu kali seminggu, dua jam maksimum pada tiap pertemuan), menggunakan metode one-to-one support dan teknik helping menurut Brammer (2003). Hasilnya menggambarkan bahwa dalam rangka memenuhi kebutuhan penderita lupus akan dukungan emosional dan dukungan informasional, tiga teknik yang sering digunakan oleh peneliti adalah attending, reassuring, summarizing; sedangkan peran yang sering dimainkan peneliti adalah peran sebagai teman yang mendengarkan, teman pemberi semangat, dan teman pemberi informasi. Deskripsi juga mengungkapkan bahwa efek dukungan sosial terhadap penderita lupus baru tampak setelah beberapa pertemuan berlangsung.